Unjuk Kerja Kotak Pendingin Termoelektrik dengan Variasi Laju Aliran Massa Air Pendingin - Mirmanto Mirmanto; Rudy Sutanto; D.K. Putra (Jurnal Teknik Mesin, 2018)
This study was taken because some conventional refrigerators still contain refrigerant comprising CFC that can support the global warming. Moreover, the construction of the conventional refrigerators is still big and heavy so that the refrigerators are difficult to be brought for traveling. The power consumed is also still high.  Therefore, friendly and low power refrigerators must be invented. A refrigerator that can fulfil the criteria is thermoelectric refrigerator. However, this type of refrigerator has a low COP. This study presents the effect of mass flow rate on the cooler box performance to examine if there is an increase in the COP. The experiments used a thermoelectric module type TEC1-12706 with an overall size of 40 mm x 40 mm x 3.74 mm. The module was placed on the top side of the cooler box. The cooler box dimension was 24.5 cm x 20 cm x 28.5 cm. The data in the test were recorded using a DAQ MX 9714 NI data logger that was connected to a PC using the LabView program. The water mass flow rates used were varied; 5 g/s, 10 g / s, and 15 g/s and the electric power employed was 41,87 W. The results show that the higher mass flow rate used does not guaranty to increase the refrigerator performance. This is due to low ranges of the mass flow rates applied. Therefore, a further investigation needs to be conducted.